Biodiversity of tamaulipan thornscrub in relation to fragmentation - Jurado, Enrique; Cuellar, Gerardo; Flores, Mercedes; González, Ignacio (1999)
Tamaulipan thornscrub has often been removed in northeastern Mexico to give way to agriculture and induced grasslands for cattle. This results in over 90% of thorn scrub being either removed or severely modified, with a few remaining fragments varying in size and distance to nearby fragments (isolation). Fragment size ranges from isolated trees in induced buffel grasslands to 300 ha of "continuous vegetation